Crosslinked amino chitosan as well as preparation and application thereof
Crosslinking chitosan with glutaraldehyde to prepare crosslinked aminochitosan, solving the problem of difficult removal of phenoxycarboxylic acid compounds in water, achieving efficient adsorption and rapid removal, and having good biocompatibility and recyclability.
Patent Information
- Application Number
- CN202510245308.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-04
Smart Images

Figure CN119735715A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water treatment, and in particular relates to cross-linked amino chitosan and preparation and application thereof. Background Art
[0002] Chitosan is a natural amino polysaccharide with abundant sources, renewable, non-toxic and side effects, good biocompatibility and degradability. Chitosan and its derivatives have many unique physiological and pharmacological functional properties and are widely used in medicine, food, pollutant adsorption and other fields. Chitosan itself has adsorption properties, is non-toxic and non-polluting, and can be used as a modification object in order to develop secondary lead compounds.
[0003] Phenoxycarboxylic acid compounds are commonly used as herbicides and plant growth regulators in agriculture, with a wide range of uses and large amounts. Phenoxycarboxylic acid compounds have a certain solubility in water. Phenoxycarboxylic acid compounds remaining in the soil and on the surface of plants are easily migrated with water, causing surface water and groundwater pollution. Phenoxycarboxylic acid compounds are difficult to degrade and have a long residual time. They have potential "three-hazard" effects, which seriously affect water quality safety and human health. Using chitosan cross-linked products to adsorb and remove residual phenoxycarboxylic acid compounds in water is of great significance for water pollution control and remediation. Summary of the invention
[0004] The purpose of the invention is to provide a cross-linked amino chitosan and its preparation and application.
[0005] To achieve the above object, the technical solution adopted by the present invention is: A cross-linked amino chitosan, wherein the cross-linked amino chitosan is represented by formula (1): N -Ethylamino chitosan is cross-linked with glutaraldehyde; Formula (1); wherein n represents the degree of polymerization, and the average value range of n is 10-12000.
[0006] A method for preparing cross-linked amino chitosan comprises reacting chitosan with phthalic anhydride to protect the amino group at the C-2 position of chitosan to obtain amino-protected chitosan; reacting the amino-protected chitosan with 4-methylbenzenesulfonyl chloride to obtain 6-p-methylbenzenesulfonylamino-protected chitosan; and then reacting the 6-p-methylbenzenesulfonylamino-protected chitosan with ethylenediamine to obtain the chitosan shown in formula (1). N -Ethylaminochitosan, N -Ethylamino chitosan and glutaraldehyde are cross-linked to obtain cross-linked amino chitosan.
[0007] The amino protected chitosan is: chitosan and phthalic anhydride are dissolved in N,N-dimethylformamide, react at 80-120°C for 6-12h under nitrogen protection, precipitate with ethanol after reaction, wash the precipitate with ethanol and filter to obtain filter cake, dry to constant weight to obtain amino-protected chitosan; wherein the amount of phthalic anhydride added is 2-8 times the molar amount of raw chitosan, N, N -The added amount of dimethylformamide is 50-100 times the molar amount of the raw material chitosan.
[0008] The 6-p-methylbenzenesulfonylamino protected chitosan is prepared by dissolving amino protected chitosan and 4-methylbenzenesulfonyl chloride in N,N -dimethylformamide, add triethylamine, react at 0°C for 2-6h, precipitate with ethanol after the reaction, wash the precipitate with ethanol and filter to obtain a filter cake, dry to constant weight, and obtain 6-p-methylbenzenesulfonylamino protected chitosan; wherein the amount of 4-methylbenzenesulfonyl chloride added is 5-10 times the molar amount of amino protected chitosan, and the amount of triethylamine added is 2-6 times the molar amount of amino protected chitosan, N,N -The added amount of dimethylformamide is 50-100 times the molar amount of amino-protected chitosan.
[0009] Said N -Ethylamino chitosan is prepared by dissolving 6-p-methylbenzenesulfonylamino protected chitosan in dimethyl sulfoxide, adding ethylenediamine, reacting at 60-100°C for 6-12h, precipitating with ethanol after the reaction, washing the precipitate with ethanol, and filtering to obtain a filter cake, which is then dried to a constant weight. N -ethylamino chitosan; wherein the amount of ethylenediamine added is 5-10 times the molar amount of 6-p-methylbenzenesulfonylamino protected chitosan, and the amount of dimethyl sulfoxide added is N -50-100 times the molar amount of ethylamino chitosan.
[0010] The cross-linked amino chitosan is: N -ethylamino chitosan is dissolved in an acetic acid aqueous solution, reacted with glutaraldehyde at room temperature for 1-5 hours, adjusted to neutrality by adding sodium hydroxide solution, then precipitated with anhydrous ethanol, and then washed with distilled water and anhydrous ethanol, filtered to obtain a filter cake, and dried to constant weight to obtain cross-linked amino chitosan; wherein the amount of glutaraldehyde added is 2-10 times the molar amount of amino chitosan, the concentration of the acetic acid aqueous solution is 1%-10%, and the volume of the acetic acid aqueous solution is N -10-30 times the molar amount of ethylamino chitosan.
[0011] An application of the cross-linked amino chitosan, and an application of the cross-linked amino chitosan as a pollutant adsorbent.
[0012] The cross-linked amino chitosan is used as an adsorbent for phenoxycarboxylic acid compounds in the environment.
[0013] The cross-linked amino chitosan is used as an adsorbent for phenoxycarboxylic acid compounds in water environments.
[0014] The phenoxycarboxylic acid compound is one or more of 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid and 2-(2,4-dichlorophenoxy) propionic acid.
[0015] A method for adsorbing phenoxycarboxylic acid compounds in an environment, wherein the cross-linked amino chitosan is added to a sample to be treated to adsorb the phenoxycarboxylic acid compounds in the sample at 15-45° C., thereby removing pollutants in the sample. The amount of the cross-linked amino chitosan added is 500-1200 mg / L.
[0016] Furthermore, the cross-linked amino chitosan is added to the sample to be treated to adsorb 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid, and 2-(2,4-dichlorophenoxy) propionic acid in the sample at 15-45° C., thereby removing pollutants in the sample. The concentration of the aqueous solution of 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid, and 2-(2,4-dichlorophenoxy) propionic acid is 50-250 mg / L, and the amount of cross-linked amino chitosan added is 500-1200 mg / L.
[0017] After the adsorption treatment, the cross-linked amino chitosan is separated and collected for application.
[0018] The advantages of the present invention are: (1) Preparation of chitosan by chemical modification N -ethylamino chitosan, the cross-linked amino chitosan prepared after cross-linking has a porous structure, an increased specific surface area, and further increased adsorption sites, and the adsorption performance of phenoxycarboxylic acid compounds in water is further improved.
[0019] (2) The cross-linked amino chitosan prepared by the present invention maintains the original good biocompatibility and biodegradability of chitosan, and at the same time has a fast adsorption speed and a large adsorption amount for phenoxycarboxylic acid compounds in water, which is significantly higher than that of chitosan and cross-linked chitosan. In addition, the cross-linked amino chitosan can be recycled, which enhances the adsorption performance of chitosan and expands the application range of chitosan. It can be widely used in water treatment and pollutant adsorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention provides a flow chart for synthesizing amino chitosan represented by formula (1).
[0021] Figure 2 This is an infrared spectrum of the raw material chitosan provided in an embodiment of the present invention.
[0022] Figure 3 This is an infrared spectrum of the amino-protected chitosan provided in an embodiment of the present invention.
[0023] Figure 4 This is an infrared spectrum of the 6-p-methylbenzenesulfonylamino protected chitosan provided in an embodiment of the present invention.
[0024] Figure 5 The embodiment of the present invention provides N -Infrared spectrum of ethylamino chitosan.
[0025] Figure 6 The embodiment of the present invention provides N -C NMR spectrum of ethylamino chitosan.
[0026] Figure 7 This is an infrared spectrum of the cross-linked amino chitosan provided in an embodiment of the present invention.
[0027] Figure 8 This is a carbon nuclear magnetic resonance spectrum of the cross-linked amino chitosan provided in an embodiment of the present invention.
[0028] Fig. 9 This is a scanning electron microscope image of the chitosan provided by the present invention.
[0029] Fig.10 This is a scanning electron microscope image of the cross-linked amino chitosan provided by the present invention.
[0030] Fig.11 The results are as follows: the adsorption amount of 2,4-dichlorophenoxyacetic acid by the cross-linked amino chitosan provided by the present invention changes over time.
[0031] Fig.12 This is an infrared spectrum of the cross-linked amino chitosan provided by the present invention after adsorbing 2,4-dichlorophenoxyacetic acid. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with examples and application examples. It should be noted that the specific implementation methods described herein are only for illustrating and explaining the present invention and are not limited to the present invention. Example 1
[0033] like Figure 1 The amino chitosan prepared is a derivative of formula (1): (1) Preparation of amino-protected chitosan: Weigh 5.8 g (36 mmol) of chitosan (see Figure 2 ) and 10.6 g (72 mmol) of phthalic anhydride were dissolved in 200 mL N,N-dimethylformamide, stirred at 80℃ for 12h. After the reaction, the reaction solution was poured into excess anhydrous ethanol to precipitate. The precipitate was filtered, washed with ethanol, and dried at 65℃ to obtain amino-protected chitosan (see Figure 3 ).
[0034] (2) Dissolve 3.2 g (11 mmol) of amino-protected chitosan obtained in step (1) in 60 mL N,N -dimethylformamide, then add 3.1mL (22mmol) triethylamine; 10.4g (55mmol) 4-methylbenzenesulfonyl chloride is added to the amino-protected chitosan solution, and reacted at 0℃ for 6h. After the reaction is completed, the reaction solution is poured into excess anhydrous ethanol to precipitate. The precipitate is filtered, washed with ethanol, and dried at 65℃ to obtain 6-p-methylbenzenesulfonylamino-protected chitosan (see Figure 4 ).
[0035] (3) 0.88 g (2 mmol) of 6-p-methylbenzenesulfonylamino protected chitosan obtained in step (2) was dissolved in 10 mL of dimethyl sulfoxide, and then 0.6 mL (10 mmol) of ethylenediamine was added, and the mixture was reacted at 60°C for 12 h. After the reaction, the reaction solution was poured into an excess of anhydrous ethanol to precipitate. The precipitate was filtered, washed with ethanol, and dried at 65°C to obtain N -Ethylamino chitosan (see Figure 5 and Figure 6 ).
[0036] (4) The obtained product in step (3) N 1.0 g (5 mmol) of -ethylamino chitosan was dissolved in 80 ml of acetic acid solution (5%), 2 ml of glutaraldehyde solution (50%) was added to the above solution, and stirred at room temperature for 5 h. After the reaction was completed, sodium hydroxide solution was used to adjust the solution to neutrality, and excess anhydrous ethanol was used to precipitate the precipitate. The precipitate was filtered, washed with anhydrous ethanol, and dried at 65 °C to obtain amino cross-linked chitosan (see Figure 7 and Figure 8 ). The obtained product is a yellow solid.
[0037] Figure 2 Infrared spectrum of raw material chitosan: 1600.6cm -1 It is the bending vibration absorption peak of NH2.
[0038] Figure 3 Infrared spectrum of amino-protected chitosan: 1710.5cm -1 and 1776.4cm -1 It is the characteristic absorption peak of C=O on the anhydride, 720.8cm -1 The above data analysis proves that amino-protected chitosan is successfully synthesized.
[0039] Figure 4 The infrared spectrum of chitosan protected by 6-p-methylbenzenesulfonylamino group: 1711.1cm -1 and 1775.8cm -1 It is the characteristic absorption peak of C=O on the anhydride, 722.1cm -1 The above data analysis proves that the synthesis of 6-p-methylbenzenesulfonylamino protected chitosan is successful.
[0040] Figure 5 for N -Infrared spectrum of ethylamino chitosan: 1711.1cm -1 、1775.8cm -1 and 722.1cm -1 The peak disappears at 1602.8cm -1 It is the bending vibration absorption peak of NH2.
[0041] Figure 6 for N -Carbon NMR spectrum of ethylamino chitosan: 104.52-59.32ppm is the characteristic peak of carbon on chitosan, 41.12ppm is N -Characteristic absorption peak of carbon on ethylamino group. The above data analysis proves N -Ethylamino chitosan was successfully synthesized.
[0042] Figure 7 Infrared spectrum of cross-linked amino chitosan: 1602.8cm -1 The peak of 1647.0cm disappeared -1 It is the characteristic absorption peak of C=N.
[0043] Figure 8 The carbon NMR spectrum of cross-linked amino chitosan: 148.63ppm is the characteristic peak of carbon in C=N; 101.81-58.61ppm is the characteristic peak of carbon on chitosan, 34.13ppm is N -Characteristic absorption peak of carbon on ethylamino group. The above data analysis proves that the synthesis of cross-linked amino chitosan is successful. Example 2
[0044] like Figure 1 The amino chitosan prepared is a derivative of formula (1):
[0045] (1) Preparation of amino-protected chitosan: 5.8 g (36 mmol) chitosan and 31.8 g (216 mmol) phthalic anhydride were weighed and dissolved in 140 mL N,N-dimethylformamide, stirred at 12℃ for 6h. After the reaction, the reaction solution was poured into excess anhydrous ethanol to precipitate. The precipitate was filtered, washed with ethanol, and dried at 65℃ to obtain amino-protected chitosan.
[0046] (2) Dissolve 3.2 g (11 mmol) of amino-protected chitosan obtained in step (1) in 42 mL N,N -dimethylformamide, then add 9.3mL (66mmol) triethylamine; 20.8g (110mmol) 4-methylbenzenesulfonyl chloride is added to the amino-protected chitosan solution, and reacted at 0℃ for 2h. After the reaction is completed, the reaction solution is poured into excess anhydrous ethanol to precipitate. The precipitate is filtered, washed with ethanol, and dried at 65℃ to obtain 6-p-methylbenzenesulfonylamino-protected chitosan.
[0047] (3) 0.88 g (2 mmol) of 6-p-methylbenzenesulfonylamino protected chitosan obtained in step (2) was dissolved in 10 mL of dimethyl sulfoxide, and then 1.2 mL (20 mmol) of ethylenediamine was added, and the mixture was reacted at 100°C for 6 h. After the reaction, the reaction solution was poured into an excess of anhydrous ethanol to precipitate. The precipitate was filtered, washed with ethanol, and dried at 65°C to obtain N -Ethylaminochitosan.
[0048] (4) The obtained product in step (3) N 1.0 g (5 mmol) of -ethylamino chitosan was dissolved in 150 ml of acetic acid solution (1%), 10 ml of glutaraldehyde solution (50%) was added to the above solution, and stirred at room temperature for 1 hour. After the reaction was completed, it was adjusted to neutral with sodium hydroxide solution, precipitated with excess anhydrous ethanol, filtered, washed with anhydrous ethanol, and dried at 65°C to obtain amino-crosslinked chitosan. The obtained product was a yellow solid. Example 3
[0049] like Figure 1 The amino chitosan prepared is a derivative of formula (1): (1) Preparation of amino-protected chitosan: 5.8 g (36 mmol) chitosan and 21.2 g (144 mmol) phthalic anhydride were weighed and dissolved in 200 mL N,N -dimethylformamide, stirred at 100℃ for 8h. After the reaction, the reaction solution was poured into excess anhydrous ethanol to precipitate. The precipitate was filtered, washed with ethanol, and dried at 65℃ to obtain amino-protected chitosan.
[0050] (2) Dissolve 3.2 g (11 mmol) of amino-protected chitosan obtained in step (1) in 84 mL N,N-dimethylformamide, and then add 6.2mL (44mmol) triethylamine; 16.6g (88mmol) 4-methylbenzenesulfonyl chloride is added to the above amino-protected chitosan solution, and reacted at 0℃ for 4h. After the reaction is completed, the reaction solution is poured into excess anhydrous ethanol to precipitate. The precipitate is filtered, washed with ethanol, and dried at 65℃ to obtain 6-p-methylbenzenesulfonylamino-protected chitosan.
[0051] (3) 0.88 g (2 mmol) of 6-p-methylbenzenesulfonylamino protected chitosan obtained in step (2) was dissolved in 10 mL of dimethyl sulfoxide, and then 1.0 mL (16 mmol) of ethylenediamine was added, and the mixture was reacted at 80°C for 8 h. After the reaction, the reaction solution was poured into an excess of anhydrous ethanol to precipitate. The precipitate was filtered, washed with ethanol, and dried at 65°C to obtain N -Ethylaminochitosan.
[0052] (4) The obtained product in step (3) N 1.0 g (5 mmol) of -ethylamino chitosan was dissolved in 50 ml of acetic acid solution (10%), 5 ml of glutaraldehyde solution (50%) was added to the above solution, and stirred at room temperature for 3 h. After the reaction, sodium hydroxide solution was used to adjust to neutrality, and excess anhydrous ethanol was used to precipitate. The precipitate was filtered, washed with anhydrous ethanol, and dried at 65 ° C to obtain amino cross-linked chitosan. The obtained product is a yellow solid. Application Example 1
[0053] Specific surface area test The pore specific surface areas of the raw chitosan and the cross-linked amino chitosan obtained in Examples 1-3 were tested using the BET specific surface area detection method. The test results are as follows: Table 1 Specific surface area of chitosan and cross-linked amino chitosan
[0054] As can be seen from Table 1, the specific surface area of the cross-linked amino chitosan obtained in Examples 1-3 is 23.49-21.69 m 2 / g, which is larger than the specific surface area of chitosan. A larger specific surface area is beneficial to improving the adsorption capacity of cross-linked amino chitosan. Application Example 2
[0055] Surface morphology test The surface morphology of chitosan and the cross-linked amino chitosan obtained in Example 1 was recorded using a scanning electron microscope (see Fig. 9 and Fig.10 ). Fig. 9 This is a scanning electron microscope image of chitosan. There are basically no holes on the surface of chitosan. Fig.10The scanning electron microscope image of the cross-linked amino chitosan obtained in Example 1 shows that the surface of the cross-linked amino chitosan is a porous structure, which is conducive to improving the adsorption capacity of the cross-linked amino chitosan. Meanwhile, the cross-linked amino chitosan obtained in Examples 2 and 3 also have corresponding characteristics. Application Example 3
[0056] Adsorption performance determination (1) Determination of the adsorption performance of cross-linked amino chitosan to phenoxycarboxylic acid compounds obtained in Example 1: A 0.2 g / L aqueous solution of 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid or 2-(2,4-dichlorophenoxy) propionic acid was prepared respectively, 50 and 100 mg of the cross-linked amino chitosan obtained in Example 1 were weighed respectively, 100 mL of the above-obtained aqueous solution of 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid or 2-(2,4-dichlorophenoxy) propionic acid was added thereto respectively, and stirred at room temperature for 2 h. The concentrations of 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid and 2-(2,4-dichlorophenoxy) propionic acid in the solution were measured. t (Note: All samples were tested three times and the average value was taken).
[0057] Adsorption capacity q t =(C0-C t )×100 / m Wherein C0 is the initial concentration of 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid, and 2-(2,4-dichlorophenoxy)propionic acid solution, and m is the amount of cross-linked amino chitosan added.
[0058] The results of the adsorption of cross-linked amino chitosan on 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid and 2-(2,4-dichlorophenoxy) propionic acid are as follows: Table 2 Adsorption performance of cross-linked amino chitosan for phenoxycarboxylic acid compounds
[0059] As can be seen from Table 2, in 100 mL of 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid or 2-(2,4-dichlorophenoxy) propionic acid solution, when the cross-linked amino chitosan obtained in Example 1 is added in an amount of 50 mg, the adsorption capacity can reach 309 mg / g, 256 mg / g, 255 mg / g and 374 mg / g respectively. This indicates that the cross-linked amino chitosan obtained in Example 1 has a high adsorption capacity for these four phenoxycarboxylic acid herbicides. At the same time, the cross-linked amino chitosan obtained in Examples 2 and 3 also has corresponding characteristics.
[0060] (2) Determination of the adsorption of 2,4-dichlorophenoxyacetic acid by cross-linked amino chitosan over time: Prepare 0.2 g / L 2,4-dichlorophenoxyacetic acid aqueous solutions, weigh 100 mg of the cross-linked amino chitosan obtained in Example 1, add it to 100 mL of 2,4-dichlorophenoxyacetic acid aqueous solution, stir at room temperature, take samples at 1 min, 2 min, 5 min, 10 min, 20 min, 30 min, 40 min, 60 min, 2 h, 3 h, and 4 h, and measure the concentration of 2,4-dichlorophenoxyacetic acid in the solution. t (Note: All samples were tested three times and the average value was taken) (See Fig.11 ).
[0061] Adsorption capacity q t =(C0-C t )×100 / m Wherein C0 is the initial concentration of the 2,4-dichlorophenoxyacetic acid aqueous solution, and m is the amount of cross-linked amino chitosan added.
[0062] The results of the adsorption of 2,4-dichlorophenoxyacetic acid by cross-linked amino chitosan over time are as follows: Fig.11 The adsorption amount of 2,4-dichlorophenoxyacetic acid by cross-linked amino chitosan remained basically unchanged after 1 hour, indicating that cross-linked amino chitosan can complete the rapid adsorption of 2,4-dichlorophenoxyacetic acid within 1 hour.
[0063] At the same time, cross-linked amino chitosan adsorbed for 1 hour was taken for detection (see Fig.12 ), Fig.12 This is the infrared spectrum of cross-linked amino chitosan adsorbing 2,4-dichlorophenoxyacetic acid for 1 hour: 1477.3cm -1 is the deformation vibration peak of OH in 2,4-dichlorophenoxyacetic acid, 1040.7cm -1 It is the stretching vibration peak of CO in 2,4-dichlorophenoxyacetic acid. The above data analysis proves that 2,4-dichlorophenoxyacetic acid is adsorbed on cross-linked amino chitosan.
[0064] (3) Determination of the effect of cross-linked amino chitosan dosage on adsorption performance: The adsorption capacity of cross-linked amino chitosan under different input conditions was measured and compared (Table 3): A 2,4-dichlorophenoxyacetic acid aqueous solution with a concentration of 0.2 g / L was prepared. 50, 80, 100, and 120 mg of the cross-linked amino chitosan obtained in Examples 1-3 were weighed, respectively, added to 100 mL of 2,4-dichlorophenoxyacetic acid aqueous solution, stirred at room temperature for 2 h, and the concentration of 2,4-dichlorophenoxyacetic acid in the solution was measured. t (Note: All samples were tested three times and the average value was taken).
[0065] Adsorption capacity q t =(C0-C t )×100 / m Adsorption rate (%) = (C0-C t )×100 / C0 Wherein C0 is the initial concentration of the 2,4-dichlorophenoxyacetic acid aqueous solution, and m is the amount of cross-linked amino chitosan added.
[0066] The results of the adsorption of 2,4-dichlorophenoxyacetic acid by cross-linked amino chitosan with different dosages: Table 3 Effect of the amount of cross-linked amino chitosan on adsorption performance
[0067] As can be seen from Table 3, in 100mL 2,4-dichlorophenoxyacetic acid aqueous solution, when the cross-linked amino chitosan input amount obtained in Example 1 is 50, 80, 100, and 120mg, the adsorption rates are 77%, 93%, 95%, and 97%, respectively. When the cross-linked amino chitosan input amount is 100mg, the adsorption rate is 95%, and when the cross-linked amino chitosan input amount is 120mg, the adsorption rate is 96%. It can be seen that increasing the amount of cross-linked amino chitosan input has little effect on the improvement of the adsorption rate. At the same time, the cross-linked amino chitosan obtained in Examples 2 and 3 also has corresponding characteristics, so the input amount of 100mg is selected as the optimal condition.
[0068] (4) Determination of the effect of 2,4-dichlorophenoxyacetic acid aqueous solution concentration on the adsorption performance of cross-linked amino chitosan: The adsorption capacity of cross-linked amino chitosan in 2,4-dichlorophenoxyacetic acid aqueous solutions with different concentrations was measured and compared (Table 4): 2,4-dichlorophenoxyacetic acid aqueous solutions with concentrations of 0.05 g / L, 0.1 g / L, 0.15 g / L, 0.2 g / L, and 0.25 g / L were prepared respectively. 100 mg of the cross-linked amino chitosan obtained in Example 1-3 was weighed and added to 100 mL of the prepared 2,4-dichlorophenoxyacetic acid aqueous solutions with different concentrations, stirred at room temperature for 2 h, and the concentration C of 2,4-dichlorophenoxyacetic acid in the solution was measured. t (Note: All samples were tested three times and the average value was taken).
[0069] Adsorption capacity q t =(C0-C t )×100 / m Adsorption rate (%) = (C0-C t )×100 / C0 Wherein C0 is the initial concentration of the 2,4-dichlorophenoxyacetic acid aqueous solution, and m is the amount of cross-linked amino chitosan added.
[0070] Determination results of the adsorption of cross-linked amino chitosan in aqueous solutions of 2,4-dichlorophenoxyacetic acid at different concentrations: Table 4 Effect of 2,4-dichlorophenoxyethyl aqueous acid solution concentration on the adsorption performance of cross-linked amino chitosan
[0071] As can be seen from Table 4, in 100 mL of 0.05 g / L, 0.1 g / L, 0.15 g / L, 0.2 g / L, and 0.25 g / L 2,4-dichlorophenoxyacetic acid aqueous solutions, when the amount of cross-linked amino chitosan obtained in Example 1 was 100 mg, the adsorption rates were 99%, 98%, 97%, 95%, and 92%, respectively. The adsorption rate of the cross-linked amino chitosan obtained in Example 1 gradually decreased with the increase of the concentration of the 2,4-dichlorophenoxyacetic acid aqueous solution. When the concentration of the 2,4-dichlorophenoxyacetic acid aqueous solution was 0.25 g / L, the adsorption rate of the cross-linked amino chitosan obtained in Example 1 was low, and the cross-linked amino chitosan obtained in Examples 2 and 3 also had corresponding characteristics, so the concentration of 0.2 g / L of the 2,4-dichlorophenoxyacetic acid aqueous solution was selected as the condition for testing the adsorption performance of the cross-linked amino chitosan.
[0072] (5) Determination of the effect of adsorption temperature on the adsorption performance of cross-linked amino chitosan: The adsorption capacity of cross-linked amino chitosan at different temperatures was measured and compared (Table 5): A 2,4-dichlorophenoxyacetic acid aqueous solution with a concentration of 0.2 g / L was prepared. 100 mg of the cross-linked amino chitosan obtained in Example 1-3 was weighed and added to 100 mL of the prepared 2,4-dichlorophenoxyacetic acid aqueous solution, and stirred at 15°C, 25°C, 35°C, and 45°C for 2 h, and the concentration of 2,4-dichlorophenoxyacetic acid in the solution was measured. t (Note: All samples were tested three times and the average value was taken).
[0073] Adsorption capacity q t =(C0-C t )×100 / m Wherein C0 is the initial concentration of the 2,4-dichlorophenoxyacetic acid aqueous solution, and m is the amount of cross-linked amino chitosan added.
[0074] Determination results of the adsorption of 2,4-dichlorophenoxyacetic acid by cross-linked amino chitosan at different temperatures: Table 5 Effect of adsorption temperature on the adsorption performance of cross-linked amino chitosan
[0075] As can be seen from Table 5, the cross-linked amino chitosans obtained in Examples 1-3 all have relatively high adsorption capacities for 2,4-dichlorophenoxyacetic acid.
[0076] (6) Determination of the reusability of cross-linked amino chitosan: The adsorption capacity of the cross-linked amino chitosan after recycling as an adsorbent for 2,4-dichlorophenoxyacetic acid was measured and compared (Table 6): A 2,4-dichlorophenoxyacetic acid aqueous solution with a concentration of 0.2 g / L was prepared. 100 mg of the cross-linked amino chitosan obtained in Example 1-3 was weighed and added to 100 mL of the prepared 2,4-dichlorophenoxyacetic acid aqueous solution, stirred at room temperature for 2 h, and the concentration of 2,4-dichlorophenoxyacetic acid in the solution was measured. t After adsorption treatment, the solution was filtered and separated to obtain cross-linked amino chitosan, which was added to anhydrous ethanol and stirred for 1 h after drying. The cross-linked amino chitosan was filtered, separated, dried, and added to 100 mL of the prepared 2,4-dichlorophenoxyacetic acid aqueous solution as an adsorbent, stirred at room temperature for 2 h, and the concentration of 2,4-dichlorophenoxyacetic acid in the solution was measured. t The above process was repeated and the concentration of 2,4-dichlorophenoxyacetic acid in the solution was determined after each adsorption (Note: the samples were measured three times and the average value was taken).
[0077] Adsorption rate (%) = (C0-C t )×100 / C0 Where C0 is the initial concentration of the 2,4-dichlorophenoxyacetic acid aqueous solution.
[0078] Test results of the reusability of cross-linked amino chitosan: Table 6 Determination of the recyclability of cross-linked amino chitosan
[0079] As can be seen from Table 6, the cross-linked amino chitosan obtained in Example 1-3 can be used as an adsorbent for 2,4-dichlorophenoxyacetic acid and still maintains a relatively high adsorption performance after being recycled five times.
[0080] The results show that cross-linked amino chitosan has a high adsorption capacity for 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid or 2-(2,4-dichlorophenoxy) propionic acid. The adsorption capacity of 2,4-dichlorophenoxyacetic acid is high in 2,4-dichlorophenoxyacetic acid solutions with different input amounts and concentrations and at different adsorption temperatures, and it can be recycled many times.
[0081] The above application examples are preferred application modes of the present invention, but the present invention is not limited to the above application examples. Any other changes, modifications, substitutions and combinations made in accordance with the essence and principles of the present invention are equivalent replacement modes and are included in the protection scope of the present invention.
Claims
1. A cross-linked amino chitosan, characterized in that: The cross-linked amino chitosan is shown in formula (1): N -Ethylamino chitosan obtained by cross-linking with glutaraldehyde; Formula (1); wherein n represents the degree of polymerization, and the average value range of n is 10-12000.
2. A method for preparing the cross-linked amino chitosan according to claim 1, characterized in that: Chitosan is reacted with phthalic anhydride to protect the amino group at the C-2 position of chitosan to obtain amino-protected chitosan; the amino-protected chitosan is reacted with 4-methylbenzenesulfonyl chloride to obtain 6-p-methylbenzenesulfonylamino-protected chitosan; and then the 6-p-methylbenzenesulfonylamino-protected chitosan is reacted with ethylenediamine to obtain the chitosan shown in formula (1) N -Ethylaminochitosan, N -Ethylamino chitosan and glutaraldehyde are cross-linked to obtain cross-linked amino chitosan.
3. The method for preparing cross-linked amino chitosan according to claim 2, characterized in that: The amino protected chitosan is: chitosan and phthalic anhydride are dissolved in N,N -dimethylformamide, react at 80-120°C for 6-12h under nitrogen protection, precipitate with ethanol after reaction, wash the precipitate with ethanol and filter to obtain filter cake, dry to constant weight to obtain amino-protected chitosan; wherein the amount of phthalic anhydride added is 2-8 times the molar amount of raw chitosan, N,N -The added amount of dimethylformamide is 50-100 times the molar amount of the raw material chitosan.
4. The method for preparing cross-linked amino chitosan according to claim 2, characterized in that: The 6-p-methylbenzenesulfonylamino protected chitosan is prepared by dissolving amino protected chitosan and 4-methylbenzenesulfonyl chloride in N,N -dimethylformamide, add triethylamine, react at 0°C for 2-6h, precipitate with ethanol after the reaction, wash the precipitate with ethanol and filter to obtain a filter cake, dry to constant weight, and obtain 6-p-methylbenzenesulfonylamino protected chitosan; wherein the amount of 4-methylbenzenesulfonyl chloride added is 5-10 times the molar amount of amino protected chitosan, and the amount of triethylamine added is 2-6 times the molar amount of amino protected chitosan, N,N -The added amount of dimethylformamide is 50-100 times the molar amount of amino-protected chitosan.
5. The method for preparing cross-linked amino chitosan according to claim 2, characterized in that: Said N -Ethylamino chitosan is prepared by dissolving 6-p-methylbenzenesulfonylamino protected chitosan in dimethyl sulfoxide, adding ethylenediamine, reacting at 60-100°C for 6-12h, precipitating with ethanol after the reaction, washing the precipitate with ethanol, and filtering to obtain a filter cake, which is then dried to a constant weight. N -ethylamino chitosan; wherein the amount of ethylenediamine added is 5-10 times the molar amount of 6-p-methylbenzenesulfonylamino protected chitosan, two The amount of methyl sulfoxide added is N -50-100 times the molar amount of ethylamino chitosan.
6. The method for preparing cross-linked amino chitosan according to claim 2, characterized in that: The cross-linked amino chitosan is: N -ethylamino chitosan is dissolved in an acetic acid aqueous solution, reacted with glutaraldehyde at room temperature for 1-5 hours, adjusted to neutrality by adding sodium hydroxide solution, then precipitated with anhydrous ethanol, and then washed with distilled water and anhydrous ethanol, filtered to obtain a filter cake, and dried to constant weight to obtain cross-linked amino chitosan; wherein the amount of glutaraldehyde added is 2-10 times the molar amount of amino chitosan, the concentration of the acetic acid aqueous solution is 1%-10%, and the volume of the acetic acid aqueous solution is N -10-30 times the molar amount of ethylamino chitosan.
7. An application of the cross-linked amino chitosan according to claim 1, characterized in that: The cross-linked amino chitosan is used as a pollutant adsorbent.
8. The use of cross-linked amino chitosan according to claim 7, characterized in that: The cross-linked amino chitosan is used as an adsorbent for phenoxycarboxylic acid compounds in the environment.
9. The use of cross-linked amino chitosan according to claim 8, characterized in that: The phenoxycarboxylic acid compound is one or more of 2,4-dichlorophenoxyacetic acid, 2-chlorophenoxyacetic acid, 4-chlorophenoxyacetic acid and 2-(2,4-dichlorophenoxy) propionic acid.
10. The use of cross-linked amino chitosan according to claim 9, characterized in that: After adsorption treatment, the cross-linked amino chitosan is separated and collected for application.
Citation Information
Patent Citations
Preparation of chitosan molecular imprinting adsorbing agent
CN101298039A
High-oxidation-resistant phenolic chitosan Schiff base, preparation method and applications thereof
CN110256605A
Aminopyridine-containing carboxymethyl chitosan as well as preparation method and application thereof
CN112442141A
Application of chitosan cross-linked product
CN115196710A
Broad-spectrum chitosan-based adsorbent as well as preparation method and application thereof
CN118045580A